Intelligence elsewhere spies and espionage outside the anglosphere - Davies, Philip H.J; Gustafson, Kristian 1974-
With contributions by leading intelligence experts for each country, the chapters give the reader important insights into intelligence culture, current practice, and security sector reform. As the world morphs into an increasingly multi-polar system, it is more important than ever to understand the national intelligence systems of rising powers and regional powers that differ significantly from those of the US, its NATO allies, and its traditional opponents. This fascinating book shines new light into intelligence practices in regions that, until now, have eluded our understanding.